2006
DOI: 10.1002/uog.2805
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional ultrasound assessment of the cervix for predicting time to spontaneous onset of labor and time to delivery in prolonged pregnancy

Abstract: Objectives To determine whether three-dimensional (3D) ultrasound including power Doppler examination of the cervix is useful for predicting time to spontaneous onset of labor or time to delivery in prolonged pregnancy. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…A correlation between ultrasound cervical length and the spontaneous onset of labor at term10–12 and in prolonged pregnancies13, 14 has been reported previously. Strobel et al studied 97 women at 42 weeks and found that cervical length is an independent predictor of the spontaneous onset of labor13.…”
Section: Discussionmentioning
confidence: 53%
“…A correlation between ultrasound cervical length and the spontaneous onset of labor at term10–12 and in prolonged pregnancies13, 14 has been reported previously. Strobel et al studied 97 women at 42 weeks and found that cervical length is an independent predictor of the spontaneous onset of labor13.…”
Section: Discussionmentioning
confidence: 53%
“…With the popularity of 3D ultrasounds, it is possible to more easily and precisely measure cervical volume 16, 17. Much research is being published on cervical volume using 3D imaging 18-20, but only one study has reported the value of cervical volume for predicting the onset of spontaneous labor at full term 14. However, this study's focus was on postterm pregnant women (≥ 41+5 gestational weeks) and the number of participants was quite small (n=60).…”
Section: Discussionmentioning
confidence: 99%
“…13,19 However, magnetic resonance imaging is not a practical imaging modality in pregnancy, and our goal was to investigate a sonographically based method. Others have used 3D sonography to measure the cervical length, 20,21 predict the time to spontaneous labor, 22 and predict the success of prostaglandin induction 23 in prolonged pregnancy. In this present study, 3D sonography was used to show cervical shape changes associated with both normal and abnormal pregnancy.…”
Section: Discussionmentioning
confidence: 99%